Effect of high DHA and ARA fortification on lipid oxidation of infant formula powder - Hong-Xin Jia; Ye-Zhi Qu; Wen-Liang Chen; Mi-Ya Su (CyTA - Journal of Food)
Our objective was to assess the impact of fortified high-dose docosahexaenoic acid (DHA) and arachidonic acid (ARA) in infant formula powders (IFs) on stability. We compared and evaluated the stability of IFs containing high and low doses of DHA and ARA over a 6-month storage period at 37°C. While most formulations showed minimal changes in unsaturated fatty acid content of during storage, significant losses of DHA and ARA were observed in some high-dose formulations. Furthermore, this study noted consistent trends in the changes of vitamin C and vitamin E across both formula groups. Notably, the high-dose group formulas exhibited a higher presence of volatile organic compounds (VOCs) during storage, along with a more pronounced increase in thiobarbituric acid-reactive substance values (TBARS). In conclusion, the inclusion of high doses of DHA and ARA in IFs may compromise their oxidative stability.